Effects of stance angle on postural stability and performance with national-standard air pistol competitors - Hawkins, R. N. (European Journal of Sport Science, 2013)
The effects of stance angle on postural stability and shooting processes were studied using eight national-standard male air-pistol shooters. Each shooter performed 60 shots each in four stance angles (0°, 15°, 30° and 45° from the line of fire). Postural stability was determined by measuring change in centre of pressure with a dual-force platform system assessing centre-of-pressure (COP) excursion (average difference of the centre of pressure from the mean) and COP speed (total COP path divided by time). Shooting process measures were determined by using a NOPTEL ST-2000 optoelectronic system. Score was assessed with a Sius Ascor S10 electronic scoring system. The results revealed no significant difference among the various stance angles; COP excursion or COP speed, p>0.05. Results indicated a significant stance angle effect with the shooting process measure, hit fine (percentage of hold within an area the size of the 10-ring when centred over the actual shot; p = 0.025) and the shooting performance measure adjusted score (raw score adjusted for true zero; p=0.008). Moreover, best overall performance was with a stance angle of 15°. These findings suggest that stance angle may affect pistol stability and performance in air-pistol athletes.